2015
DOI: 10.1186/s12862-015-0557-0
|View full text |Cite
|
Sign up to set email alerts
|

Tooth and scale morphogenesis in shark: an alternative process to the mammalian enamel knot system

Abstract: BackgroundThe gene regulatory network involved in tooth morphogenesis has been extremely well described in mammals and its modeling has allowed predictions of variations in regulatory pathway that may have led to evolution of tooth shapes. However, very little is known outside of mammals to understand how this regulatory framework may also account for tooth shape evolution at the level of gnathostomes. In this work, we describe expression patterns and proliferation/apoptosis assays to uncover homologous regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(77 citation statements)
references
References 62 publications
4
73
0
Order By: Relevance
“…Developing body denticles are highly proliferative units similar to teeth and dental lamina [40, 42] (Fig. 8j–l).…”
Section: Resultsmentioning
confidence: 99%
“…Developing body denticles are highly proliferative units similar to teeth and dental lamina [40, 42] (Fig. 8j–l).…”
Section: Resultsmentioning
confidence: 99%
“…Bemis et al (2015) suggested that the pair of small cusps that develop on both sides of the crown in juvenile white sharks is not homologous to the lateral cusplets of other lamniform sharks, because the cusps of juvenile white sharks seem to develop by a process that is different from the lateral cusplet development of other lamniform sharks, and thus, should be renamed "serrational cusplets." We feel that their hypothesis should be supported by further evidence such as gene expression patterns related to the formation of lateral cusplets in tooth development (e.g., Debiais-Thibaud et al, 2015). We do not discuss the homology of this structure here, and follow the great majority of previous studies in using the term "lateral cusplets.…”
Section: Dental Terminologymentioning
confidence: 92%
“…It is still unclear whether signaling centers are apomorphies of mammals and drive the bud‐cap transition or participate in tooth shape formation in nonmammalian species. In the shark Scyliorhinus canicula , a chondrychthian, cytologically distinct structures reminiscent of mammalian EKs have been observed . The folded tip of the epithelial bud is formed by slowly proliferating cells, but apoptosis has not been detected.…”
Section: Introductionmentioning
confidence: 99%
“…The folded tip of the epithelial bud is formed by slowly proliferating cells, but apoptosis has not been detected. However, co‐expression of Shh and Fgf8 orthologs is present in this area . In reptiles, structures resembling primary EKs have been indicated in the alligator, which has single cuspid teeth, and also in several squamate species with both single and multicuspid teeth .…”
Section: Introductionmentioning
confidence: 99%